Calculation Of Schmitt Triggers Depending On Input Threshold Voltages, The Inverse Problem - Martirosyan, S. G.; Torikyan, J. E. («Պոլիտեխնիկ» տպ.)
The way and features of solving the inverse problem of calculating inverting and non-inverting classical Schmitt triggers are presented. Equations have been derived in which the input threshold voltages are known as the main and constant parameters, while the other parameters are secondary to the threshold voltages. All the other unknown parameters of the trigger circuit are calculated. Ներկայացված են Շմիտտի շրջող և չշրջող դասական տրիգերների հաշվարկի հակադարձ խնդրի լուծման ճանապարհը և առանձնահատկությունները: Արտածվել են նոր հավասարումներ, որոնցում հայտնի են մուտքային շեմային լարումները`որպես գլխավոր և անփոփոխ պարամետրեր, իսկ մյուս պարամետրերը երկրորդական են շեմային լարումների համեմատ: Представлены путь и особенности решения обратной задачи расчета инвертирующих и неинвертирующих классических триггеров Шмитта. Получены уравнения, в которых входные пороговые напряжения известны как основные и постоянные параметры, а остальные параметры являются вторичными по отношению к пороговым напряжениям.
Keywords: Microelectronics